Reminder from Allah: panorama of pandemic as a parable - Muhsin, Sayyed Mohamed (Mission Soft Foundation, 2023)
Let’s reflect on what God wants us to acquire from this dreadful global crisis. Though the pandemic posed severe disorder to the world, we can reasonably perceive that the pre-pandemic world order was also in grave disorder and affected by infectious ethical viruses. Many people were treated with unpardonable injustice. Innocent people were killed and burnt to death. Some had to flee their homeland and start a new life in a new world but as a refugee. Based on religion, race, colour and ethnicity, citizens were treated differently as some were elite while some were second-class. Some endangered lives of several species and posed severe threats to the ecosystem. The pandemic made us taste the bitterness of disorder that millions go through without any reason around us on a daily basis. We were scared of infection and its concomitant risks. We kept ourselves as the top priority. We tried to take no chances. Nobody seemed to avail. It exposed our vulnerability, helplessness and susceptibility. The pandemic taught us to refrain from several harmful things and be extra-cautious in our choices and preferences. Absent-minded people’s risk was not trivial.